Comparison of the Impact of Zika and Dengue Virus Infection, and Other Acute Illnesses of Unidentified Origin on Cognitive Functions in a Prospective Cohort in Chiapas Mexico - Belaunzarán-Zamudio, Pablo F.; Ortega-Villa, Ana M.; Mimenza-Alvarado, Alberto J.; Guerra-De-Blas, Paola Del Carmen; Aguilar-Navarro, Sara G.; Sepúlveda-Delgado, Jesús; Hunsberger, Sally; Salgado, Raydel Valdés; Ramos-Castañeda, José; Rincón León, Héctor Armando; Rodríguez de La Rosa, Paul; Nájera Cancino, José Gabriel; et al. (Frontiers in Neurology, 2021)
Zika has been associated with a variety of severe neurologic manifestations including meningitis and encephalitis. We hypothesized that it may also cause mild to subclinical neurocognitive alterations during acute infection or over the long term. In this observational cohort study, we explored whether Zika cause subclinical or mild neurocognitive alterations, estimate its frequency and duration, and compare it to other acute illnesses in a cohort of people with suspected Zika infection, in the region of Tapachula in Chiapas, Mexico during 2016-2018. We enrolled patients who were at least 12 years old with suspected Zika virus infection and followed them up for 6 months. During each visit participants underwent a complete clinical exam, including a screening test for neurocognitive dysfunction (Montreal Cognitive Assessment score). We enrolled 406 patients (37 with Zika, 73 with dengue and 296 with other acute illnesses of unidentified origin (AIUO). We observed a mild and transient impact over cognitive functions in patients with Zika, dengue and with other AIUO. The probability of having an abnormal MoCA score (<26 points) was significantly higher in patients with Zika and AIUO than in those with dengue. Patients with Zika and AIUO had lower memory scores than patients with dengue (Zika vs Dengue: -0.378, 95%CI-0.678 to -0.078; p=0.014: Zika vs AIUO 0.264, 95%CI 0.059, 0.469; p=0.012). The low memory performance in patients with Zika and AIUO accounts for most of the differences in the overall MoCA score when compared with patients with dengue. Our results show a decrease in cognitive function during acute illness and provides no evidence to support the hypothesis that Zika might cause neurocognitive alterations longer than the period of acute infection or different to other infectious diseases. While effects on memory or perhaps other cognitive functions over the long term are possible, larger studies using more refined tools for neurocognitive functioning assessment are needed to identify these. Trial Registration: NCT02831699